The Effect of Gelatin Addition from Various Fish Skin to the Physical and Chemical Properties of Chikuwa - Irvan, Muhammad (Program Studi Teknologi Pangan, 2019)
Chikuwa is one of Japanese traditional fishery food product that commonly made from potato starch, fish surimi, and some spices. To enhance Chikuwa physical and chemical properties especially in texture attribute and protein content, Gelatin can be added. Gelatin is a partial hydrolysis protein that usually added in food making process to improve the gumminess quality and the protein content. Gelatin can be derived from bone collagen, skin and fish scale. The purpose of this study is to analyze the effect of gelatin from various skin fish to the physical and chemical characteristics of Chikuwa. The research method used is experimental laboratories using a completely randomized design (CRD) with 3 replications. The data analysed with ANOVA and continued with BNJ analysis if there is a significant difference between the treatments. This research has divided into two stages. The first step aim is to make the gelatin from the skin of seabass, payus fish and tilapia with 3% concentrations. The second step is Chikuwa making added with gelatin. The parameters that observed are water content, protein content, white degree, gel strength, sensory attributes, folding, bite. The results showed that Chikuwa with the addition of gelatin from seabass, payus and tilapia skin are significantly different (p lt;0.05) due to the physical and chemical characteristics of Chikuwa. The best Chikuwa quality is Chikuwa with the addition of seabass gelatin, where the gelatin yield is 18.03 ± 0.68; the gelatin gel strength is 251.11 ± 1.08 bloom; the viscosity is 5.80 ± 0.15 cP; the gel Chikuwa sample strength is 954.54 ± 0.56 gcm and protein content is 22.01 ± 0.98%